Sexual Dynamics of Iranian Remarried Women in Blended Families: A Qualitative Study on Remarried Women's Life. Issue 5 (4th July 2019) - Musavi, Somayeh; Fatehizade, Maryam; Jazayeri, Rezvanossadat
ABSTRACT: Despite the indispensable importance of the sexual relationship to the family dynamics, there has never been a study on remarried Iranian women in blended families. For the purpose of this study, 52 divorced women, who married for the second time, were interviewed. The data were codified line by line using thematic content analysis. Six main themes were identified from the interviews: (a) intrapersonal effects, (b) interpersonal effects, (c) attachment-based sexual relationships, (d) a new start, (e) family-related stress, and (f) pregnancy-related issues. Many of these women reported they were still thinking about their previous relationship and were influenced especially by how their ex-husband evaluated their body image. These findings presented a relatively clear image of the impact of remarriage on the sexuality of Iranian remarried women in blended families. These findings suffer from some constraints, such as generalizing of the data due to the small sample size.